Composite material, related device and preparation method of carrier transport composite film

By using a composite material of oxide semiconductor nanomaterials, polydiallyldimethylammonium chloride and organic solvents, combined with pH adjustment and long-chain ligand addition, the problem of poor density of the electron transport layer is solved and high efficiency is achieved. electron transport and improved light-emitting device performance.

CN119331460APending Publication Date: 2025-01-21GUANGDONG JUHUA PRINTING DISPLAY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310909208.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The electron transport layer prepared by oxide semiconductor nanomaterials has poor density and low electron transport efficiency.

Method used

A composite material including oxide semiconductor nanomaterials, polydiallyldimethylammonium chloride and organic solvents is used. By adjusting the pH value and adding long-chain ligands, the oxide semiconductor nanomaterials are ionized and electrostatically adsorbed to form Dense electron transport layer.

Benefits of technology

The density and electron transmission efficiency of the electron transport layer are improved, and the electrical properties of the light-emitting device are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331460A_ABST
    Figure CN119331460A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of display, and relates to a composite material. The composite material comprises an oxide semiconductor nanomaterial, poly (diallyldimethylammonium chloride) and an organic solvent. The invention also relates to a luminescent device, a display device and a preparation method of the carrier transport composite film. According to the technical scheme provided by the invention, the prepared electron transport layer has relatively high compactness, so that the electron transport efficiency of the electron transport layer can be improved, and the performance of the light-emitting device is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and more specifically, to a composite material, a related device, and a method for preparing a carrier transport composite film. Background Art

[0002] Light-emitting devices generally have a cathode, a light-emitting layer, a charge transport layer, and an anode layer. However, these light-emitting devices usually have the problem of unbalanced charge transport. By setting an electron transport layer between the cathode and the light-emitting layer, better electron transport between the cathode and the light-emitting layer can be achieved. However, the electron transport layer prepared by the existing oxide semiconductor nanomaterials has poor density and low electron transport efficiency of the film layer, resulting in low electrical performance of the light-emitting device. Summary of the invention

[0003] The technical problem to be solved by the embodiments of the present application is that the electron transport layer prepared by oxide semiconductor nanomaterials has poor density and low electron transport efficiency.

[0004] In order to solve the above technical problems, the present application also provides a composite material, which adopts the following technical solution:

[0005] A composite material comprises: oxide semiconductor nanomaterial, polydiallyldimethylammonium chloride and an organic solvent.

[0006] Furthermore, the pH value of the composite material is higher than the isoelectric point of the oxide semiconductor nanomaterial.

[0007] Furthermore, the surface of the oxide semiconductor nanomaterial is bound to a long-chain ligand; the long-chain ligand is selected from at least one of a chain hydrocarbon with 1-30 carbon atoms, a carboxylic acid with 1-30 carbon atoms, an amine with 1-30 carbon atoms, a thiol with 1-30 carbon atoms, and a phosphorus-containing organic compound with 1-30 carbon atoms, which is unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, or cyano.

[0008] Furthermore, the organic solvent includes at least one of an alcohol solvent, an alcohol ether solvent, and an ester solvent; and / or,

[0009] The mass ratio of the oxide semiconductor nanomaterial, the polydiallyldimethylammonium chloride and the organic solvent is (20-30): (5-10): (60-75); and / or,

[0010] The long-chain ligand is selected from at least one of carboxylic acids with 10 to 30 carbon atoms, thiols with 8 to 30 carbon atoms, amines with 8 to 30 carbon atoms, and phosphorus-containing organic compounds with 20 to 30 carbon atoms, which are unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, and cyano groups;

[0011] The isoelectric point of the oxide semiconductor nanomaterial is 2-4; and or

[0012] The pH value of the composite material is 8-9.

[0013] Further, the alcohol solvent is selected from at least one of a monohydric alcohol and a dihydric alcohol; the alcohol ether solvent includes a dihydric alcohol ether ester solvent; the ester solvent includes a dihydric alcohol ester solvent; and / or,

[0014] The mass ratio of the oxide semiconductor nanomaterial, the polydiallyldimethylammonium chloride and the organic solvent is (25-30): (5-10): (60-70); and / or,

[0015] The oxide semiconductor nanomaterial is selected from at least one of ZnO, TiO2, Ta2O3, ZrO2, NiO and SnO2; and / or,

[0016] The oxide semiconductor nanomaterial is selected from at least one of undoped or doped TiLiO, ZnAlO, ZnMgO, ZnSnO, ZnLiO and InSnO, wherein the doped element includes at least one of Li, Mg, Sn, Al, Ag, Mn and F.

[0017] In order to solve the above technical problems, the present application also provides a method for preparing a carrier transport composite film, which adopts the following technical solution:

[0018] A preform, an adsorption solution, and a composite material are provided, wherein the preform includes a cathode, or the preform includes an anode, a hole functional layer, and a light-emitting layer stacked in sequence from bottom to top, the material of the adsorption solution includes a cationic polyelectrolyte; and the composite material includes an oxide semiconductor nanomaterial, polydiallyldimethylammonium chloride, and an organic solvent;

[0019] The adsorption solution is disposed on the cathode of the preform, or the adsorption solution is disposed on the light-emitting layer of the preform to obtain an adsorption layer;

[0020] The composite material is arranged on the adsorption layer to obtain an electron transport layer, thereby preparing the carrier transport composite film.

[0021] Further, the cationic polyelectrolyte includes polydiallyldimethylammonium chloride;

[0022] The preparation method of the adsorption solution comprises:

[0023] Dissolving polydiallyldimethylammonium chloride in a polar protic solvent to obtain the adsorption solution; wherein the adsorption solution comprises the following combination calculated by weight: 1-50 parts of polydiallyldimethylammonium chloride and 50-99 parts of the polar protic solvent; and / or,

[0024] The pH value of the adsorption solution is 8-9.

[0025] Furthermore, the step of placing the adsorption solution on the cathode or the light-emitting layer to prepare the adsorption layer specifically includes:

[0026] The adsorption solution is placed on the cathode or the light-emitting layer, and after standing for a preset time, it is spun off to remove the polar protic solvent, so that the polydiallyldimethylammonium chloride forms the adsorption layer on the cathode or the light-emitting layer; and / or,

[0027] The polar protic solvent includes at least one of water, liquid ammonia, methanol, ethanol, tert-butyl alcohol, benzyl alcohol, formic acid and acetic acid.

[0028] Furthermore, after the step of arranging the composite material on the adsorption layer, the method further comprises:

[0029] The polydiallyldimethylammonium chloride and the organic solvent are removed to solidify the oxide semiconductor nanomaterial on the adsorption layer.

[0030] In order to solve the above technical problems, the embodiment of the present application provides a light emitting device, which adopts the following technical solution:

[0031] A light-emitting device, comprising an anode, a hole functional layer, a light-emitting layer, and a cathode stacked in sequence, characterized in that it also comprises:

[0032] An adsorption layer, located between the light-emitting layer and the cathode, wherein the material of the adsorption layer comprises a cationic polyelectrolyte;

[0033] An electron transport layer, disposed on the adsorption layer and located between the adsorption layer and the cathode, or between the light-emitting layer and the adsorption layer;

[0034] The ink of the electron transport layer comprises oxide semiconductor nanomaterials, polydiallyldimethylammonium chloride and an organic solvent.

[0035] Further, the cationic polyelectrolyte comprises polydiallyldimethylammonium chloride; and / or,

[0036] The thickness of the adsorption layer is 1-5 nm; and / or,

[0037] The thickness of the electron transport layer is 30-40 nm; and / or,

[0038] The material of the anode layer and / or cathode layer includes one or more of metal, carbon material and metal oxide, the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or

[0039] The light emitting device further comprises an electron injection layer, which is located between the electron transport layer and the cathode layer; the material of the electron injection layer comprises an inorganic material and / or an organic material; the inorganic material is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, aluminum zinc oxide, manganese zinc oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped element comprises one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds; and / or

[0040] The light-emitting layer is a quantum dot light-emitting layer or an organic light-emitting layer; the material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnS At least one of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, wherein the Group IV-VI compound is selected from SnS, SnSe, SnTe, PbS, PbSe, Pb At least one of SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, wherein the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlP At least one of As, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or

[0041] The core of the core-shell structured quantum dots includes any one of the above-mentioned single-structured quantum dots, and the shell material of the core-shell structured quantum dots includes at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and the above-mentioned single-structured quantum dots; the material of the organic light-emitting layer includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distyrene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives; and / or

[0042] The light-emitting device also includes a hole functional layer, which is arranged between the light-emitting layer and the anode layer. The hole functional layer includes a hole transport layer and / or a hole injection layer. When the hole functional layer includes a stacked hole transport layer and a hole injection layer, the hole transport layer is arranged adjacent to the light-emitting layer, and the hole injection layer is arranged adjacent to the anode layer; the hole injection layer is located between the hole transport layer and the anode layer; the material of the hole transport layer and / or the hole injection layer includes at least one of TFB, CuPc, PVK, Poly-TPD, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tri(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and C60.

[0043] In order to solve the above technical problems, the embodiment of the present application further provides a display device, which adopts the following technical solution:

[0044] A display device comprises a light-emitting device as described in any of the above schemes.

[0045] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0046] The composite material provided in the present application can be used for the solution method preparation of the electron transport layer. The present application adds polydiallyldimethylammonium chloride to the composite material. The polydiallyldimethylammonium chloride in the material causes the oxide semiconductor nanomaterial to have a negative charge on the surface due to ionization. The oxide semiconductor nanomaterial with a negative charge can cooperate with other film layers with a positive charge to produce an electrostatic adsorption effect. The oxide semiconductor nanomaterial is tightly arranged under the electrostatic adsorption effect, reducing the gaps between the material particles, so that the prepared electron transport layer has a higher density, thereby improving the electron transport efficiency of the electron transport layer and further improving the performance of the light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the scheme of the present application, a brief introduction is given below to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0048] Figure 1 is a schematic structural diagram of a carrier transport composite film provided by an embodiment of the present application;

[0049] Figure 2 is a schematic structural diagram of a light-emitting device provided by an embodiment of the present application;

[0050] Figure 3 is a schematic structural diagram of a light-emitting device provided by another embodiment of the present application;

[0051] Figure 4 is a flow chart of a method for preparing a carrier transport composite film provided by an embodiment of the present application;

[0052] Figure 5 yes Figure 3 Specific steps of S100 are shown in the flowchart.

[0053] Reference numerals:

[0054] 100, adsorption layer; 200, electron transport layer; 300, cathode layer; 400, light-emitting layer; 500, substrate; 600, hole transport layer; 700, hole injection layer; 800, anode layer. DETAILED DESCRIPTION

[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.

[0056] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0057] An embodiment of the present application provides a composite material, which includes: an oxide semiconductor nanomaterial, polydiallyldimethylammonium chloride and an organic solvent.

[0058] It can be understood that polydiallyldimethylammonium chloride (PDDA) has the characteristic of carrying a positive charge within a wide pH range. When the composite material contains polydiallyldimethylammonium chloride, the positively charged polydiallyldimethylammonium chloride can cause the oxide semiconductor nanomaterials in the composite material to migrate in the electric field, produce ionization, and make the surface of the oxide semiconductor nanomaterials in the ink have a negative charge.

[0059] The composite material provided in this embodiment can be used for the solution method preparation of the electron transport layer. By adding polydiallyl dimethyl ammonium chloride (PDDA) to the material, polydiallyl dimethyl ammonium chloride (PDDA) can cause the oxide semiconductor nanomaterial in the ink to be ionized under certain conditions and carry a negative charge. The oxide semiconductor nanomaterial with a negative charge can cooperate with other film layers with a positive charge to produce an electrostatic adsorption effect. The oxide semiconductor nanomaterial is closely arranged under the electrostatic adsorption effect, reducing the gaps between the material particles, so that the prepared electron transport layer has a higher density, thereby improving the electron transport efficiency of the electron transport layer and further improving the performance of the light-emitting device.

[0060] In this embodiment, the pH value of the composite material is higher than the isoelectric point of the oxide semiconductor nanomaterial.

[0061] It can be understood that since polydiallyldimethylammonium chloride has the characteristic of carrying a positive charge in a wide pH range, when the pH value of the composite material is higher than the isoelectric point of the oxide semiconductor nanomaterial, polydiallyldimethylammonium chloride remains positively charged, and the positively charged polydiallyldimethylammonium chloride will cause the oxide semiconductor nanomaterial to ionize at this time, thereby making the surface of the oxide semiconductor nanomaterial negatively charged.

[0062] In this embodiment, long-chain ligands are bound to the surface of the oxide semiconductor nanomaterial.

[0063] Oxide semiconductor nanomaterials generally need to be bound to organic ligands on the surface to improve stability and solubility, wherein the organic ligands include short-chain ligands and long-chain ligands.

[0064] Generally, oxide semiconductor nanomaterials with short-chain ligands bound to their surfaces are more densely arranged and have higher electron transfer efficiency when forming electron transport layers than oxide semiconductor nanomaterials with long-chain ligands. However, short-chain ligands reduce the solubility of oxide semiconductor nanomaterials. Short-chain ligands make oxide semiconductor nanomaterials interact more strongly and are more prone to coagulation. As they cannot be preserved, they are difficult to use in solution methods to prepare electron transport layers. Oxide semiconductor nanomaterials with long-chain ligands bound to their surfaces are often used in the solution method preparation of electron transport layers. However, since long-chain ligands increase the solubility of oxide semiconductor nanomaterials, it also means that the oxide semiconductor nanomaterials are highly dispersed in the solvent. As a result, when the electron transport layer is prepared by the solution method, the oxide semiconductor nanomaterials in the film layer are not dense enough and the electron transfer efficiency is low, which limits the performance of quantum dot light-emitting devices.

[0065] By using the composite material provided in the present application, long-chain ligands are bonded to the surface of the oxide semiconductor nanomaterial, which ensures that the oxide semiconductor nanomaterial has a high solubility in the ink, facilitates the transportation and storage of the ink, and also makes the gaps between the oxide semiconductor nanomaterials after film formation smaller, the arrangement more dense, and the densification effect of the film layer better.

[0066] In this embodiment, the long-chain ligand is selected from at least one of chain hydrocarbons with 1-30 carbon atoms, carboxylic acids with 1-30 carbon atoms, amines with 1-30 carbon atoms, thiols with 1-30 carbon atoms, and phosphorus-containing organic compounds with 1-30 carbon atoms, which are unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, thiol, or cyano groups.

[0067] Specifically, the long-chain ligand is selected from at least one of carboxylic acids with 10 to 30 carbon atoms, thiols with 8 to 30 carbon atoms, amines with 8 to 30 carbon atoms, and phosphorus-containing organic compounds with 20 to 30 carbon atoms, which are unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, or cyano.

[0068] Specifically, the long-chain ligand can be selected from at least one of decadecanoic acid, undecenoic acid, tetradecanoic acid, oleic acid, stearic acid, octadecyl mercaptan, dodecyl mercaptan, octadecyl mercaptan, oleylamine, octadecylamine, octaamine, trioctylphosphine and trioctylphosphine oxide.

[0069] In this embodiment, the organic solvent includes at least one of an alcohol solvent, an alcohol ether solvent and an ester solvent.

[0070] Wherein, the alcohol solvent is selected from at least one of a monohydric alcohol and a dihydric alcohol;

[0071] Specifically, the alcohol solvent includes at least one of ethanol, butanol, isopropanol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,2-pentanediol and 1,4-pentanediol;

[0072] Alcohol ether solvents refer to organic compounds that have both ether bonds and hydroxyl groups in their composition.

[0073] The alcohol ether solvent is selected from glycol ether ester solvents; the glycol ether ester solvent refers to an organic compound having both an ether bond and two hydroxyl groups in its composition.

[0074] The alcohol ether solvent is selected from at least one of ethylene glycol methyl ether acetate, ethylene glycol ethyl ether acetate, ethylene glycol propyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, diethylene glycol methyl ether acetate, diethylene glycol ethyl ether acetate, dipropylene glycol methyl ether acetate, dipropylene glycol ethyl ether acetate and dipropylene glycol propyl ether acetate;

[0075] Wherein, the ester solvent is selected from diol ester solvents; the diol ester solvent refers to an ester compound containing two hydroxyl groups.

[0076] The ester solvent is selected from at least one of ethylene glycol acetate, ethylene glycol propionate, ethylene glycol butyrate, ethylene glycol valerate, ethylene glycol diacetate, propylene glycol acetate, propylene glycol propionate, propylene glycol butyrate, propylene glycol valerate, butylene glycol acetate, butylene glycol propionate, butylene glycol butyrate, butylene glycol valerate, diethylene glycol acetate, diethylene glycol propionate, diethylene glycol butyrate, and 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate.

[0077] In some embodiments, the mass ratio of the oxide semiconductor nanomaterial, the polydiallyldimethylammonium chloride, and the organic solvent is (20-30): (5-10): (60-75).

[0078] In the above-mentioned mass ratio range, the pH value of the composite material can be controlled in the range of 8-9, the pH value is higher than the isoelectric point of the added oxide semiconductor nanomaterial, the ink is weakly alkaline, and polydiallyldimethylammonium chloride (PDDA) enables the oxide semiconductor nanomaterial to be ionized in the solution and have a negative charge on the surface.

[0079] In some embodiments, the mass ratio of the oxide semiconductor nanomaterial, the polydiallyldimethylammonium chloride, and the organic solvent can be 20:5:75; or, the mass ratio of the oxide semiconductor nanomaterial, the polydiallyldimethylammonium chloride, and the organic solvent can be 25:10:65; or, the mass ratio of the oxide semiconductor nanomaterial, the polydiallyldimethylammonium chloride, and the organic solvent can be (25-30):(5-10):(60-70).

[0080] Specifically, the pH value of the composite material can be controlled by adjusting the amount of polydiallyldimethylammonium chloride added to the composite material, and / or adjusting the amount of organic solvent added to the composite material, and / or adjusting the amount of oxide semiconductor nanomaterial added to the composite material.

[0081] In this embodiment, the oxide semiconductor nanomaterial is selected from at least one of ZnO, TiO2, Ta2O3, ZrO2, NiO and SnO2;

[0082] And / or, the oxide semiconductor nanomaterial is selected from at least one of undoped or doped TiLiO, ZnAlO, ZnMgO, ZnSnO, ZnLiO and InSnO, wherein the doped element includes at least one of Li, Mg, Sn, Al, Ag, Mn and F.

[0083] In this embodiment, the oxide semiconductor nanomaterial is particles.

[0084] In this embodiment, the isoelectric point of the oxide semiconductor nanomaterial is 2-4.

[0085] It can be understood that the pH value of the oxide semiconductor nanomaterial in the composite material when the surface is uncharged is 2-4. When the pH value of the composite material is higher than the isoelectric point of the oxide semiconductor nanomaterial, the oxide semiconductor nanomaterial is easily ionized under the action of polydiallyldimethylammonium chloride, so that the surface has a negative charge. The oxide semiconductor nanomaterial with an isoelectric point of 2-4 is used to make the pH value of the composite material higher than the isoelectric point of the oxide semiconductor nanomaterial, while maintaining weak alkalinity to avoid damaging other film layers in the device.

[0086] The composite material provided in this embodiment can be used to prepare an electron transport layer.

[0087] like Figure 1 As shown, based on the above-mentioned composite material, the embodiment of the present application provides a carrier transport composite film, including:

[0088] The adsorption layer 100, the material of the adsorption layer 100 includes a cationic polyelectrolyte;

[0089] The electron transport layer 200 is disposed on the adsorption layer 100 . The electron transport layer 200 is prepared from a composite material. The composite material includes an oxide semiconductor nanomaterial, polydiallyldimethylammonium chloride and an organic solvent.

[0090] It can be understood that polydiallyldimethylammonium chloride (PDDA) has the property of being positively charged in a wide pH range, and the positively charged polydiallyldimethylammonium chloride in the composite material can ionize the oxide semiconductor nanomaterial, and the oxide semiconductor nanomaterial has a negative charge on its surface after ionization. Since the cationic polyelectrolyte on the adsorption layer 100 has a positive charge, the oxide semiconductor nanomaterial with a negative charge on its surface in the composite material disposed on the adsorption layer 100 will undergo electrostatic adsorption with the adsorption layer 100, thereby forming a dense electron transport layer 200.

[0091] The carrier transport composite film of this embodiment is provided with an electron transport layer 200 on the adsorption layer 100, so that the cationic polyelectrolyte with positive charge on the adsorption layer 100 produces an electrostatic adsorption effect on the oxide semiconductor nanomaterial with negative charge on the surface. The oxide semiconductor nanomaterial is closely arranged under the electrostatic adsorption effect, and the gaps between the material particles are reduced, so that the electron transport layer 200 has a higher density, thereby having a higher electron transport efficiency. The carrier transport composite film of the present application has both the electron transport capacity and stability provided by the oxide semiconductor nanomaterial, and has a higher density and a higher electron transport efficiency, which can effectively improve the electrical performance of the light-emitting device.

[0092] like Figure 2-3As shown, based on the above composite material, the embodiment of the present application further provides a light-emitting device, the light-emitting device comprising:

[0093] The invention comprises an anode layer 800, a hole function layer, a light emitting layer 400, and a cathode layer 300 which are stacked in sequence.

[0094] Also includes:

[0095] An adsorption layer 100 is located between the light-emitting layer 400 and the cathode layer 300, and the material of the adsorption layer 100 includes a cationic polyelectrolyte;

[0096] The electron transport layer 200 is arranged on the adsorption layer 100 and is located between the adsorption layer 100 and the cathode layer 300, or between the light-emitting layer 400 and the adsorption layer 100; the ink of the electron transport layer 200 includes oxide semiconductor nanomaterials, polydiallyldimethylammonium chloride and an organic solvent.

[0097] Diallyldimethylammonium chloride (PDDA) has the property of carrying positive charge in a wide pH range. The positively charged polydiallyldimethylammonium chloride in the composite material can ionize the oxide semiconductor nanomaterial, and the oxide semiconductor nanomaterial has a negative charge on its surface after ionization. Since the cationic polyelectrolyte on the adsorption layer 100 has a positive charge, the oxide semiconductor nanomaterial with a negative charge on its surface in the composite material disposed on the adsorption layer 100 will undergo electrostatic adsorption with the adsorption layer 100, thereby forming a dense electron transport layer 200.

[0098] The light-emitting device of this embodiment is provided with an adsorption layer 100 and an electron transport layer 200 between the light-emitting layer and the electrode layer, and the electron transport layer 200 is provided on the adsorption layer 100, so that the cationic polyelectrolyte with positive charge on the adsorption layer 100 produces an electrostatic adsorption effect on the oxide semiconductor nanomaterial with negative charge on the surface. The oxide semiconductor nanomaterial is closely arranged under the electrostatic adsorption effect, and the gap between the material particles is reduced, so that the electron transport layer 200 has a higher density, thereby having a higher electron transport efficiency. The carrier transport composite film of the present application has both the electron transport ability and stability provided by the oxide semiconductor nanomaterial, and has a higher density and a higher electron transport efficiency, which can effectively improve the electrical performance of the light-emitting device.

[0099] Specifically, the anode layer 800, the hole functional layer, the light-emitting layer 400 and the cathode layer 300 of the light-emitting device may be stacked on the substrate 500 in sequence from bottom to top; or may be stacked on the substrate 500 in sequence from top to bottom.

[0100] In one embodiment, if Figure 2As shown, the anode layer 800 , the hole functional layer, the light-emitting layer 400 and the cathode layer 300 are stacked in sequence from bottom to top, the adsorption layer 100 is arranged on the light-emitting layer 400 , and the electron transport layer 200 is arranged between the adsorption layer 100 and the cathode layer 300 .

[0101] In another embodiment, if Figure 3 As shown, the anode layer 800 , the hole functional layer, the light-emitting layer 400 and the cathode layer 300 are stacked in sequence from top to bottom, the adsorption layer 100 is arranged on the cathode layer 300 , and the electron transport layer 200 is arranged between the adsorption layer 100 and the light-emitting layer 400 .

[0102] It can be understood that the light emitting device of the present application can be a front-mounted structure (such as Figure 2 As shown), it can also be a flip-chip structure provided in the embodiment of the present application (as shown Figure 3 As shown), as long as the adsorption layer 100 and the electron transport layer 200 are both arranged between the light-emitting layer 400 and the cathode layer 300, and the adsorption layer 100 is prepared before the electron transport layer 200, the electron transport layer 200 can be electrostatically adsorbed by the adsorption layer 100 when it is formed.

[0103] Specifically, the hole functional layer is arranged between the light-emitting layer 400 and the anode layer 800, and the hole functional layer includes a hole transport layer 600 and / or a hole injection layer 700. When the hole functional layer includes a stacked hole transport layer 600 and a hole injection layer 700, the hole transport layer 600 is arranged adjacent to the light-emitting layer 400, and the hole injection layer 700 is arranged adjacent to the anode layer 800; the hole injection layer 700 is located between the hole transport layer 600 and the anode layer 800; the hole transport layer 600 and / or the hole injection layer 700 are arranged adjacent to the anode layer 800. Or the material of the hole injection layer 700 includes at least one of TFB, CuPc, PVK, Poly-TPD, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tri(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and C60.

[0104] In this embodiment, the cationic polyelectrolyte includes polydiallyldimethylammonium chloride.

[0105] It is understandable that when the adsorption layer 100 is prepared by the solution method, the solution used to prepare the adsorption layer 100 needs to be set to be weakly alkaline to avoid the adsorption layer 100 from damaging other layers (such as the cathode layer 300 or the light-emitting layer 400). Polydiallyldimethylammonium chloride has a positive charge in a wide pH range. Therefore, even if the solution used to prepare the adsorption layer 100 is weakly alkaline, the polydiallyldimethylammonium chloride in the solution always has a positive charge, thereby ensuring that the adsorption layer 100 prepared by the solution method has a positive charge.

[0106] In this embodiment, the adsorption layer 100 material is polydiallyldimethylammonium chloride, so that the carrier transport composite film of the present application can be prepared on the cathode layer 300 or the light-emitting layer 400 by a solution method, and will not affect the cathode layer 300 or the light-emitting layer 400 in contact with it. Using polydiallyldimethylammonium chloride as the adsorption layer 100 material makes the carrier transport composite film more applicable, and the preparation is simpler and more efficient.

[0107] Of course, in some other embodiments, the cationic polyelectrolyte can also be independently selected from at least one of polyhexamethylene biguanide, cationic polyacrylamide, polyvinylamine and polyquaternary ammonium salt.

[0108] In some embodiments, the thickness of the adsorption layer 100 is 3-4 nm. In some embodiments, the thickness of the adsorption layer 100 can be set to 3, 3.2, 3.5, 3.8, 3.9, 4 nm. The thickness of the adsorption layer 100 is relatively thin and will not affect the overall thickness of the light-emitting device.

[0109] In some embodiments, the thickness of the electron transport layer 200 is 30-40 nm. In some embodiments, the thickness of the electron transport layer 200 can be set to 30, 32, 35, 38, or 40 nm.

[0110] In some embodiments, the material of the anode layer 800 and / or the cathode layer 300 includes one or more of a metal, a carbon material, and a metal oxide, wherein the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene, and carbon fiber; the metal oxide includes a doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, wherein the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2.

[0111] In some embodiments, the light-emitting device further comprises an electron injection layer, which is located between the electron transport layer 200 and the cathode layer 300; the material of the electron injection layer comprises an inorganic material and / or an organic material; the inorganic material is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements comprise one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds.

[0112] In some embodiments, the light-emitting layer 400 is a quantum dot light-emitting layer or an organic light-emitting layer; the material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, At least one of ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, PbS, At least one of SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, wherein the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, At least one of AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or

[0113] The core of the core-shell structured quantum dots includes any one of the above-mentioned single-structure quantum dots, and the shell material of the core-shell structured quantum dots includes at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and the above-mentioned single-structured quantum dots; the material of the organic light-emitting layer includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distyrene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.

[0114] Based on the above-mentioned light-emitting device, an embodiment of the present application provides a display device, which includes the light-emitting device described in any of the above-mentioned embodiments.

[0115] like Figure 4 As shown, based on the above-mentioned carrier transport composite film, an embodiment of the present application provides a method for preparing a carrier transport composite film, the method comprising:

[0116] S100, providing prefabricated parts, adsorption solutions, and composite materials;

[0117] Wherein, the preform includes a cathode, or the preform includes an anode, a hole functional layer and a light-emitting layer stacked in sequence from bottom to top; the material of the adsorption solution includes a cationic polyelectrolyte; the composite material includes an oxide semiconductor nanomaterial, polydiallyldimethylammonium chloride and an organic solvent;

[0118] S200, disposing the adsorption solution on the cathode of the preform, or disposing the adsorption solution on the light-emitting layer of the preform to obtain an adsorption layer;

[0119] S300, disposing the composite material on the adsorption layer to obtain an electron transport layer, thereby preparing a carrier transport composite film.

[0120] It can be understood that in this embodiment, after the adsorption solution containing cationic polyelectrolyte is prepared to form the adsorption layer 100, the adsorption layer 100 is made to have a positive charge. Since polydiallyldimethylammonium chloride has the characteristic of having a positive charge in a wide pH range, the pH value of the composite material containing oxide semiconductor nanomaterials and polydiallyldimethylammonium chloride is higher than the isoelectric point of the oxide semiconductor nanomaterials. At this time, the polydiallyldimethylammonium chloride in the composite material will promote the ionization of the oxide semiconductor nanomaterials, so that the oxide semiconductor nanomaterials have a negative charge.

[0121] When a composite material containing negatively charged oxide semiconductor nanomaterials is disposed on an adsorption layer 100 with a positive charge, the oxide semiconductor nanomaterials in the ink will be electrostatically adsorbed by the positive charge of the adsorption layer 100. Under the action of electrostatic adsorption, the oxide semiconductor nanomaterials reduce the distance between material particles, thereby forming tightly arranged oxide semiconductor nanomaterial particles, and preparing a more dense electron transport layer 200, thereby obtaining a carrier transport composite film with higher electron transport efficiency.

[0122] In the carrier transport composite film prepared by the method provided in this embodiment, the high density of the electron transport layer 200 is achieved by the adsorption between the oxide semiconductor nanomaterial on the electron transport layer and the adsorption layer 100. Therefore, the density of the electron transport layer 200 will not be affected by the solubility of the oxide semiconductor nanomaterial in the composite material, so that the electron transport layer 200 can be prepared using oxide semiconductor nanomaterials with higher solubility. Therefore, the method provided in this application can take into account the high solubility of the oxide semiconductor nanomaterial in the ink to meet the needs of ink preservation, while also ensuring that the prepared electron transport layer 200 has a high density and improves the electron transport efficiency of the electron transport layer.

[0123] In this embodiment, the cationic polyelectrolyte includes polydiallyldimethylammonium chloride.

[0124] like Figure 5 As shown, step S100 specifically includes:

[0125] S110, dissolving polydiallyldimethylammonium chloride in a polar protic solvent to obtain the adsorption solution.

[0126] The adsorption solution comprises the following combination calculated in parts by weight: 1-50 parts of polydiallyldimethylammonium chloride and 50-99 parts of polar protic solvent.

[0127] S120, mixing oxide semiconductor nanomaterials, polydiallyldimethylammonium chloride and an organic solvent to prepare a composite material.

[0128] It can be understood that the adsorption solution can ensure that the polydiallyldimethylammonium chloride in the solution has a positive charge within the above weight percentage calculation range. In particular, since polydiallyldimethylammonium chloride has the characteristic of having a positive charge within a wide pH value range, the pH value of the adsorption solution can be adjusted so that when the adsorption solution is disposed on the light-emitting layer or the cathode, the performance of the light-emitting layer or the cathode will not be damaged, and at the same time, the adsorption layer can be ensured to have a positive charge.

[0129] Specifically, in some embodiments, the combination of weight parts of the adsorption solution can be set to: 1 part of polydiallyldimethylammonium chloride and 99 parts of polar protic solvent; or, 20 parts of polydiallyldimethylammonium chloride and 80 parts of polar protic solvent; or, 50 parts of polydiallyldimethylammonium chloride and 50 parts of polar protic solvent.

[0130] In this embodiment, the pH value of the adsorption solution is 8-9.

[0131] When the adsorption solution is within the above pH range, the cathode or the light-emitting layer below will not be damaged when preparing the adsorption layer, and the adsorption layer exhibits the characteristic of being positively charged.

[0132] In some embodiments, the pH value of the adsorption solution can be set to 8, 8.5 or 9 by adjusting the ratio of polydiallyldimethylammonium chloride and polar protic solvent.

[0133] Specifically, in some embodiments, the adsorption solution may include the following combination calculated by weight: 10-15 parts of polydiallyldimethylammonium chloride and 85-90 parts of polar protic solvent, so as to control the pH value of the adsorption solution in the range of 8-9.

[0134] In some embodiments, in order to control the pH value of the adsorption solution in the range of 8-9, the combination of weight parts of the adsorption solution can be set to: 10 parts of polydiallyldimethylammonium chloride and 90 parts of polar protic solvent; or, 12 parts of polydiallyldimethylammonium chloride and 87 parts of polar protic solvent; or, 15 parts of polydiallyldimethylammonium chloride and 85 parts of polar protic solvent.

[0135] In some embodiments, the polar protic solvent includes at least one of water, liquid ammonia, methanol, ethanol, tert-butyl alcohol, benzyl alcohol, formic acid and acetic acid.

[0136] In this embodiment, the polar protic solvent is deionized water.

[0137] In this embodiment, step S200 specifically includes:

[0138] The adsorption solution is disposed on the cathode of the preform, or the adsorption solution is disposed on the light-emitting layer of the preform, and after standing for a preset time, the solution is spun dry to remove the polar protic solvent, so that the polydiallyldimethylammonium chloride forms the adsorption layer on the cathode or the light-emitting layer.

[0139] Specifically, polydiallyldimethylammonium chloride is dissolved in deionized water to obtain an adsorption solution; the adsorption solution is set on the cathode or the light-emitting layer, and after standing for 1-10 minutes, it is spun at high speed to remove the water in the solution, and an adsorption layer formed by polydiallyldimethylammonium chloride with positive charge is obtained. The solvent (such as deionized water) is completely removed by high-speed drying. Compared with the drying method, the drying method can avoid the volatilization of polydiallyldimethylammonium chloride, and maintain the positive charge characteristic of polydiallyldimethylammonium chloride, and can maintain the flatness of the adsorption layer. The adsorption solution is left on the cathode or the light-emitting layer for a preset time, so that the polydiallyldimethylammonium chloride in the adsorption solution can be deposited on the cathode or the light-emitting layer, and then spun at a preset speed to remove only the water and allow the polydiallyldimethylammonium chloride to be deposited and retained in the light-emitting layer or the cathode layer, thereby obtaining an adsorption layer containing only polydiallyldimethylammonium chloride.

[0140] In this embodiment, in step S300, after the step of disposing the composite material on the adsorption layer, the step further includes:

[0141] The polydiallyldimethylammonium chloride and the organic solvent are removed to solidify the oxide semiconductor nanomaterial on the adsorption layer.

[0142] Specifically, step S300 includes:

[0143] The composite material is arranged on the adsorption layer and annealed at a preset temperature to volatilize the polydiallyldimethylammonium chloride and the organic solvent to remove the polydiallyldimethylammonium chloride and the organic solvent in the composite material, so that the oxide semiconductor nanomaterial is solidified on the adsorption layer to form an electron transport layer, thereby preparing a carrier transport composite film.

[0144] In this embodiment, annealing is used to volatilize PDDA and the organic solvent to obtain an electron transport layer consisting only of oxide semiconductor nanomaterials.

[0145] In some embodiments, the annealing at a preset temperature specifically includes:

[0146] The process is performed at a first temperature for a first time, and then at a second temperature for a second time.

[0147] The first temperature can be set to 90-110°C, and the corresponding first time can be 20-40 minutes;

[0148] The second temperature may be set to 140-160° C., and the corresponding second time may be 50-120 min.

[0149] It can be understood that the composite material is disposed on the adsorption layer and annealed at the first temperature for the first time, which is conducive to the orderly arrangement of the oxide semiconductor nanomaterial on the adsorption layer due to the electrostatic adsorption of positive and negative charges. Annealing at the second temperature for the second time can ensure that the PDDA and organic solvent in the composite material are completely volatilized, thereby obtaining an electron transport layer with a stable structure, dense arrangement and uniformity.

[0150] The carrier transport composite film provided in the above embodiments of the present application can be prepared by the method for preparing the carrier transport composite film provided in any of the above embodiments.

[0151] The present invention will be further described below in conjunction with specific embodiments:

[0152] Example 1

[0153] The preparation of the carrier transport composite film of the quantum dot light-emitting device of this embodiment includes the following steps:

[0154] Step 1: 10 g of PDDA was mixed with 90 ml of deionized water to obtain a PDDA aqueous solution with a pH of 8, and the solution was deposited on the quantum dot light-emitting layer by inkjet printing. After standing for 5 minutes, the solution was spun dry at a speed of 4000 rpm to obtain an adsorption layer with a thickness of 3 nm.

[0155] Step 2: 25g of nano zinc oxide particles, 68g of 1,2-propylene glycol and 7g of PDDA were mixed evenly to obtain a composite material with a pH of 8.3, wherein the ligand of the nano zinc oxide particles was oleylamine. The composite material was deposited on the adsorption layer by inkjet printing, annealed at 100°C for 30min, and then annealed at 150°C for 1h to form an electron transport layer, and a carrier transport composite film with a thickness of 35nm was obtained.

[0156] Example 2

[0157] The preparation of the carrier transport composite film of the quantum dot light-emitting device of this embodiment includes the following steps:

[0158] Steps 1 and 2 of this embodiment are the same as the preparation method of Example 1. The difference from Example 1 is that the ligand of the nano zinc oxide particles is dodecyl mercaptan, and the thickness of the carrier transport composite film is 36 nm.

[0159] Example 3

[0160] The preparation of the carrier transport composite film of the quantum dot light-emitting device of this embodiment includes the following steps:

[0161] Steps 1 and 2 of this embodiment are the same as the preparation method of Example 1. The difference from Example 1 is that the ligand of the nano zinc oxide particles is oleic acid, and the thickness of the carrier transport composite film is 35 nm.

[0162] Comparative Example 1

[0163] The preparation of the carrier transport composite film of the quantum dot light-emitting device of this comparative example includes the following steps:

[0164] Step 1: Mix 25g of nano zinc oxide particles and 75g of 1,2-propylene glycol to obtain a composite material. The ligand of the nano zinc oxide particles is oleylamine. Deposit the composite material solution on the quantum dot light-emitting layer by inkjet printing, anneal at 100°C for 30min, and then anneal at 150°C for 1h to obtain an electron transport layer with a thickness of 35nm.

[0165] Performance Testing

[0166] After other functional layers were deposited on the carrier transport composite films prepared in Examples 1 to 3 and Comparative Example 1 to form quantum dot light-emitting devices, device current efficiency tests and T95 life tests were performed on the quantum dot light-emitting devices.

[0167] The test results are shown in Table 1.

[0168] Table 1

[0169] Quantum dot light-emitting devices Current efficiency T95 Lifespan Example 1 2.7cd / A 133h Example 2 2.5cd / A 131h Example 3 2.8cd / A 129h Comparative Example 1 1.8cd / A 98h

[0170] It should be noted that in the device current efficiency test, the current efficiency is the ratio of unit brightness to current density; T95 life refers to the working time of the device when it is lit at room temperature and used until the luminous intensity decays to 95% of the initial value, using the lighting parameter nit of the display device.

[0171] From the results in Table 1, it can be seen that the current efficiency of the quantum dot light-emitting device formed by the carrier transport composite film prepared by the method of Examples 1-3 is above 2.5 cd / A, and the device T95 life is above 125 h. It can be seen that the preparation method provided in the embodiment of the present application is simple in process, and the prepared carrier transport composite film has good performance, so that the obtained quantum dot light-emitting device has high current efficiency and life.

[0172] Analysis of the data of Example 1 and Comparative Example 1 shows that the current efficiency and T95 life of Comparative Example 1 are not as good as those of Example 1, which indicates that the quantum dot light-emitting device formed by the carrier transport composite film provided in the embodiments of the present application has better overall performance, indicating that the electron transport layer in the carrier transport composite film of Example 1 has better film performance.

[0173] According to the above test results, it can be explained that by adding PDDA to the composite material and adjusting to a suitable pH, the nano zinc oxide particles are made negatively charged. Under the action of the electrostatic adsorption of the adsorption layer, the distance between the nano zinc oxide particles is reduced, and an electron transport layer with a more dense and uniform arrangement and a more stable structure can be formed.

[0174] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.

Claims

1. A composite material, characterized in that: include: Oxide semiconductor nanomaterials, polydiallyldimethylammonium chloride and organic solvents. 2 . The composite material according to claim 1 , wherein the pH value of the composite material is higher than the isoelectric point of the oxide semiconductor nanomaterial.

3. The composite material according to claim 1, characterized in that The surface of the oxide semiconductor nanomaterial is bound to a long-chain ligand; the long-chain ligand is selected from at least one of a chain hydrocarbon with 1 to 30 carbon atoms, a carboxylic acid with 1 to 30 carbon atoms, an amine with 1 to 30 carbon atoms, a thiol with 1 to 30 carbon atoms, and a phosphorus-containing organic compound with 1 to 30 carbon atoms, which is unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, or cyano.

4. The composite material according to claim 1, characterized in that The organic solvent includes at least one of an alcohol solvent, an alcohol ether solvent, and an ester solvent; and / or, The mass ratio of the oxide semiconductor nanomaterial, the polydiallyldimethylammonium chloride and the organic solvent is (20-30): (5-10): (60-75); and / or, The long-chain ligand is selected from at least one of carboxylic acids with 10 to 30 carbon atoms, thiols with 8 to 30 carbon atoms, amines with 8 to 30 carbon atoms, and phosphorus-containing organic compounds with 20 to 30 carbon atoms, which are unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, and cyano groups; The isoelectric point of the oxide semiconductor nanomaterial is 2-4; and or The pH value of the composite material is 8-9.

5. The composite material according to claim 4, characterized in that The alcohol solvent is selected from at least one of monohydric alcohol and dihydric alcohol; the alcohol ether solvent is selected from dihydric alcohol ether ester solvent; the ester solvent is selected from dihydric alcohol ester solvent; and / or, The mass ratio of the oxide semiconductor nanomaterial, the polydiallyldimethylammonium chloride and the organic solvent is (25-30): (5-10): (60-70); and / or, The oxide semiconductor nanomaterial is selected from at least one of ZnO, TiO2, Ta2O3, ZrO2, NiO and SnO2; and / or, The oxide semiconductor nanomaterial is selected from at least one of undoped or doped TiLiO, ZnAlO, ZnMgO, ZnSnO, ZnLiO and InSnO, wherein the doped element includes at least one of Li, Mg, Sn, Al, Ag, Mn and F.

6. A method for preparing a carrier transport composite film, characterized in that: include: A preform, an adsorption solution and a composite material are provided, wherein the preform comprises a cathode, or the preform comprises an anode, a hole functional layer and a light-emitting layer stacked in sequence from bottom to top; the material of the adsorption solution comprises a cationic polyelectrolyte; and the composite material comprises an oxide semiconductor nanomaterial, polydiallyldimethylammonium chloride and an organic solvent; The adsorption solution is disposed on the cathode of the preform, or the adsorption solution is disposed on the light-emitting layer of the preform to obtain an adsorption layer; The composite material is arranged on the adsorption layer to obtain an electron transport layer, thereby preparing the carrier transport composite film.

7. The method for preparing a carrier transport composite film according to claim 6, characterized in that: The cationic polyelectrolyte comprises polydiallyldimethylammonium chloride; The preparation method of the adsorption solution comprises: Dissolving polydiallyldimethylammonium chloride in a polar protic solvent to obtain the adsorption solution; wherein the adsorption solution comprises the following combination calculated by weight: 1-50 parts of polydiallyldimethylammonium chloride and 50-99 parts of the polar protic solvent; and / or, The pH value of the adsorption solution is 8-9.

8. The method for preparing a carrier transport composite film according to claim 7, characterized in that: The step of placing the adsorption solution on the cathode or the light-emitting layer to prepare the adsorption layer specifically includes: The adsorption solution is placed on the cathode or the light-emitting layer, and after standing for a preset time, it is spun off to remove the polar protic solvent, so that the polydiallyldimethylammonium chloride forms the adsorption layer on the cathode or the light-emitting layer; and / or, The polar protic solvent includes at least one of water, liquid ammonia, methanol, ethanol, tert-butyl alcohol, benzyl alcohol, formic acid and acetic acid.

9. The method for preparing a carrier transport composite film according to claim 7, characterized in that: After the step of arranging the composite material on the adsorption layer, the method further comprises: The polydiallyldimethylammonium chloride and the organic solvent are removed to solidify the oxide semiconductor nanomaterial on the adsorption layer.

10. A light-emitting device, comprising an anode layer, a hole functional layer, a light-emitting layer, and a cathode layer stacked in sequence, characterized in that: Also includes: An adsorption layer, located between the light-emitting layer and the cathode layer, wherein the material of the adsorption layer comprises a cationic polyelectrolyte; An electron transport layer, disposed on the adsorption layer and located between the adsorption layer and the cathode layer, or between the light-emitting layer and the adsorption layer; The ink of the electron transport layer comprises oxide semiconductor nanomaterials, polydiallyldimethylammonium chloride and an organic solvent.

11. The light emitting device according to claim 10, characterized in that: The cationic polyelectrolyte comprises polydiallyldimethylammonium chloride; and / or, The thickness of the adsorption layer is 1-5 nm; and / or, The thickness of the electron transport layer is 30-40 nm; and / or, The material of the anode layer and / or cathode layer includes one or more of metal, carbon material and metal oxide, the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or The light emitting device further comprises an electron injection layer, which is located between the electron transport layer and the cathode layer; the material of the electron injection layer comprises an inorganic material and / or an organic material; the inorganic material is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, aluminum zinc oxide, manganese zinc oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped element comprises one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds; and / or The light-emitting layer is a quantum dot light-emitting layer or an organic light-emitting layer; the material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnS At least one of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, wherein the Group IV-VI compound is selected from SnS, SnSe, SnTe, PbS, PbSe, Pb At least one of SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, wherein the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlP At least one of As, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or The core of the core-shell structured quantum dots includes any one of the above-mentioned single-structured quantum dots, and the shell material of the core-shell structured quantum dots includes at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and the above-mentioned single-structured quantum dots; the material of the organic light-emitting layer includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distyrene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives; and / or The light-emitting device also includes a hole functional layer, which is arranged between the light-emitting layer and the anode layer. The hole functional layer includes a hole transport layer and / or a hole injection layer. When the hole functional layer includes a stacked hole transport layer and a hole injection layer, the hole transport layer is arranged adjacent to the light-emitting layer, and the hole injection layer is arranged adjacent to the anode layer; the hole injection layer is located between the hole transport layer and the anode layer; the material of the hole transport layer and / or the hole injection layer includes at least one of TFB, CuPc, PVK, Poly-TPD, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tri(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and C60.

12. A display device, characterized in that: The light emitting device comprises the light emitting device as claimed in any one of claims 10 to 11.